Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858141
|View full text |Cite
|
Sign up to set email alerts
|

The Mimesis Effect

Abstract: We present a study that investigates the heretofore unexplored relationship between a player's sense of her narrative role in an interactive narrative role-playing game and the options she selects when faced with choice structures during gameplay. By manipulating a player's knowledge over her role, and examining in-game options she preferred in choice structures, we discovered what we term the Mimesis Effect: when players were explicitly given a role, we found a significant relationship between their role and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Crucially, these conflicting approaches to measuring and operationalising intrinsic motivation have quietly carried into the HCI games literature (only Phillips et al [139, p. 4] appear to concede that "there are numerous versions of the measure, with minor variations to certain items"). Some scholars (e.g., [196,62,193]), in line with the scale authors, employed the interest/enjoyment dimension only. Others matched McAuley et al, operationalising intrinsic motivation as a function of interest/enjoyment, perceived competence, effort/importance, and pressure/tension (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Crucially, these conflicting approaches to measuring and operationalising intrinsic motivation have quietly carried into the HCI games literature (only Phillips et al [139, p. 4] appear to concede that "there are numerous versions of the measure, with minor variations to certain items"). Some scholars (e.g., [196,62,193]), in line with the scale authors, employed the interest/enjoyment dimension only. Others matched McAuley et al, operationalising intrinsic motivation as a function of interest/enjoyment, perceived competence, effort/importance, and pressure/tension (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Based on their research when subjects are engaged in a racing game (Need for Speed: Carbon) they imagine themselves as if they are a driver and have the attitudes of such character, while in a shooter game (Call of Duty 2) they do so as a soldier [45]. Similarly, Dominguez et al [53] showed when a player is given a role in interactive narrative role-playing games, implicit or explicit, they remain consistent with their roles, and their chosen actions in games are under the influence of their roles. They explicitly gave roles to one group and did not do so for their control group.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that human behavior is similar across different conditions, however, this may not always be the case. In fact, other work has shown how even the player-character (see [217]) makes a difference in how people play. Therefore, further scrutiny is needed to understand under what circumstances design aspects may or may not make a difference.…”
Section: Limitationsmentioning
confidence: 99%